A Novel Approach to Determining the Turbine Discharge at Hydropower Plants with Adduction Channel - Cristian Purece; Eliza Tica; Florica Popa; Bogdan Popa (Engineering Research: Perspectives on Recent Advances Vol. 3, 2025)
Discharge is one of the most important parameters that characterize the operation of a hydroelectric power plant. Traditional methodologies determine the discharge of a high-head hydropower plant by the Gibson method, by exploring the velocity field through a penstock section (current meter method). Nevertheless, it is much more comfortable and advantageous to measure the discharge in a downstream section, at the immediately following hydropower plant, but in this case, it is necessary to know all the phenomena that occur in the tailrace channel between the two hydropower plants and to establish the measurement conditions so that the discharge estimation be within the limits imposed by the standards in force. This paper aims to determine the turbine discharge at Retezat HPP by measuring the discharge to the turbine from the HA1 in Clopotiva HPP.